Scheduling of irrigation for wheat (Triticum aestivum) under restricted water supply in Narmada region - MALIWAL, G L; PATEL, J K; KASWALA, R R; PATEL, ML; BHATNAGAR, R; PATEL, J C (The Indian Journal of Agricultural Sciences, 2013)
A field experiment was conducted during winter season (rabi) of 1994-95 to 1996 -97 at Khandha, Gujarat to studythe effect of irrigation schedule on yield and quality ufwheat (Triticum aestivum L. emend. Fiori & Paol.) under restrictedwater supply. The treatments conprised 8 levels of irrigation schedule. Results indicated that 4 irrigtations at pre-sowing,crown root initiation, tillering and flowcring under restricted watcr supply gave consistently higher grain yield of wheatduring all the years and also in pooled. The water-use efficiency was also higher with this treatment. The quality of wheatgrain (lysine and tryptophan) does not affect due to reduction in number of irrigation under constraint of irrigation waterthan normal recommended irrigation.